Perception and Use of Web 2.0 Applications by Medical Students of Ambrose Alli University Ekpoma - Ikenwe, Iguehi Joy; Idhalama, Ogagaoghene Uzezi; Ode, Christian Edokpolo (International Journal of Knowledge Content Development & Technology, 2019)
ABSTRACT This study examined the perception and use of web 2.0 applications for academic purposes by medical students of Ambrose Alli University, Ekpoma. The objective aimed to investigate the medical students perceptions of web 2.0 applications, web 2.0 tools use, extent of use and purpose for use and challenges encounter when using web 2.0 applications. Descriptive survey method was used for this study. The total population of this study was 3670 and the sample size was 367 representing 10% of the study. The purposive sampling technique was adopted as the sample technique. The instrument used for this study was questionnaire, a total of 367 copies were administered and 321 were found useful for the study. Percentage, means and standard deviation on table and chart were used to analyze the data collected using Statistical Package for the Social Sciences (SPSS) software. Findings showed that the perception of web 2.0 applications of medical students AAU was positive and few of web 2.0 applications was use for academic purposes. Findings also showed that challenges encountered by medical students using web 2.0 applications are; unstable network signal, insufficient data usage, erratic power supply, lack of open wifi connection, limited knowledge about web 2.0. It was recommended in the study that medical students should be provided with the facilities in a format more familiar to them and used by most of them and institutions needs to equip the learning process with the needed facilities which will be of utmost benefit even for future purposes URL: http://ijkcdt.net/xml/20258/20258.pdf